Experimental performance of a multi‐storey braced frame structure with non‐structural industrial components subjected to synthetic ground motions. (5th May 2022) - Nardin, Chiara; Bursi, Oreste S.; Paolacci, Fabrizio; Pavese, Alberto; Quinci, Gianluca
Abstract: The seismic risk assessment of industrial facilities mainly relies on historical data and the analysis and design of uncoupled secondary components. Accordingly, the dynamic interaction between primary structures and process equipment is overlooked. The SPIF project – Seismic Performance of Multi‐Component Systems in Special Risk Industrial Facilities – was carried out to respond to this gap, within the European H2020 SERA framework. Its objective regarded the investigation of the seismic behaviour of an archetype industrial multi‐storey steel moment resisting frame (MRF) structure equipped with non‐structural components (NSCs) by means of shaking table tests. The goal of the proposed study was to extend the interaction analysis between a primary multi‐storey braced frame (BF) steel structure and NSCs in a performance‐based earthquake engineering (PBEE) perspective. Along this vein, to excite the vibration periods of the NSCs and thus enhance possible coupling with the primary structure, a synthetic site‐based ground motion model (GMM) was employed. More precisely, the proposed research intended: (i) to severely excite the process equipment and supplement the scarcity of real records with a specific frequency content by means of a stochastic GMM; (ii) to quantify seismic‐induced force and displacement demands of secondary components and their effects on the primary BF structure. The evaluation of the experimental data clearly shows buckling in the bracing system of the BF configuration and a strong interaction between vertical tanks and floor crossbeams of the BF. At the very least, the favourable performance of the archetype BF under strong seismic records is demonstrated.